2022
DOI: 10.1016/j.jid.2021.11.032
|View full text |Cite
|
Sign up to set email alerts
|

Parallel Single-Cell Multiomics Analysis of Neonatal Skin Reveals the Transitional Fibroblast States that Restrict Differentiation into Distinct Fates

Abstract: This is a PDF file of an article that has undergone enhancements after acceptance, such as the addition of a cover page and metadata, and formatting for readability, but it is not yet the definitive version of record. This version will undergo additional copyediting, typesetting and review before it is published in its final form, but we are providing this version to give early visibility of the article. Please note that, during the production process, errors may be discovered which could affect the content, a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
26
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
6
2
1

Relationship

2
7

Authors

Journals

citations
Cited by 33 publications
(34 citation statements)
references
References 60 publications
2
26
0
Order By: Relevance
“…Single-cell transcriptomic analysis has provided an unprecedented high resolution of peritoneal immune cells including different subtypes of B cells, macrophages, and T cells. To share our data with other researchers, we have created a cloud-based web tool for easy gene searches, which does not require complicated computer programming skills 81 . The webpage for this tool is: https://kanakohayashilab.org/hayashi/en/mouse/peritoneal.immune.cells/ .…”
Section: Methodsmentioning
confidence: 99%
“…Single-cell transcriptomic analysis has provided an unprecedented high resolution of peritoneal immune cells including different subtypes of B cells, macrophages, and T cells. To share our data with other researchers, we have created a cloud-based web tool for easy gene searches, which does not require complicated computer programming skills 81 . The webpage for this tool is: https://kanakohayashilab.org/hayashi/en/mouse/peritoneal.immune.cells/ .…”
Section: Methodsmentioning
confidence: 99%
“…We focused on the “gene activity” of the cluster and the marker gene of different cell-type to validate that the established dataset was indeed represented a hair follicle population. In E13.5, we found that clusters 0, 1 and 2 mainly expressed fibroblast markers of Twist2 28 and Col1a1 29 , clusters 3 and 8 expressed keratinocytes markers of Krt14 30 and Krt15 31 , cluster 4 expressed macrophages markers of Cd86 32 and Inpp5d 33 , cluster 5 expressed schwann markers of Sox5 6 and Sox10 34 , cluster 6 expressed blood vessels markers of Pecam1 35 and Kdr 36 , 37 , cluster 7 expressed muscle markers of Pax7 30 and Cdh15 38 . In E16.5, we detected that clusters 0, 2 and 6 expressed fibroblasts markers of Twist2 and Col1a1 , cluster 1 expressed keratinocytes markers of Krt14 and Krt15 , cluster 3 and 9 expressed blood vessels markers of Kdr and Flt4 36 , cluster 4 expressed lymphocytes markers of Cpa3 39 and Ccr8 40 , cluster 5 expressed macrophages markers of Cd86 and F13a1 41 , cluster 7 expressed muscle markers of Myod1 42 and Myog 43 , cluster 8 expressed schwann markers of Gpr17 and Lims2 6 , cluster 10 expressed melanocytes markers of Tyr 6 and Dct 44 , cluster 11 expressed melanocytes markers of Ctsd 6 and Lamp1 45 .…”
Section: Technical Validationmentioning
confidence: 83%
“…In E16.5, we detected that clusters 0, 2 and 6 expressed fibroblasts markers of Twist2 and Col1a1 , cluster 1 expressed keratinocytes markers of Krt14 and Krt15 , cluster 3 and 9 expressed blood vessels markers of Kdr and Flt4 36 , cluster 4 expressed lymphocytes markers of Cpa3 39 and Ccr8 40 , cluster 5 expressed macrophages markers of Cd86 and F13a1 41 , cluster 7 expressed muscle markers of Myod1 42 and Myog 43 , cluster 8 expressed schwann markers of Gpr17 and Lims2 6 , cluster 10 expressed melanocytes markers of Tyr 6 and Dct 44 , cluster 11 expressed melanocytes markers of Ctsd 6 and Lamp1 45 . In P0, we detected that clusters 0, 2, 3, 7 and 9 mainly expressed fibroblasts markers of Twist2 and Col1a1 , clusters 1, 4, 5, 6 and 8 expressed keratinocytes markers of Krt14 and Krt15 , cluster 10 expressed melanocyte markers of Pax3 6 and Plp1 46 , cluster 11 expressed blood vessels markers of Kdr and Cdh5 30 , whereas the cells of cluster 12 expressed pericytes markers of Ebf2 30 and Rgs5 47 . According to the gene activity of marker genes, the cells were classified into 6, 8 and 5 populations, respectively.…”
Section: Technical Validationmentioning
confidence: 95%
“…We previously identified five distinct fibroblast populations in the human oral mucosa (Caetano et al, 2021); however, we found a small number of transcriptional differences which conditioned a successful mapping of these cells with traditional in situ techniques. Furthermore, scRNA-seq data does not capture cell fates but rather cell states with recent evidence suggesting that many fibroblast lineage markers reflect a fibroblast state (Thompson et al, 2021). In this study, we were able to map these fine-grained differences and observed distinct spatial enrichment.…”
Section: Discussionmentioning
confidence: 99%